Study on Sound Absorption Properties of Polyvinyl Chloride (PVC) Film Multicavity Structure Materials - Tingying Zhang; Jiyang Zhang; Pengxuan Zheng; Hong Hou; Ying Xu (Shock and Vibration)
Since the development of industry, sound absorption and noise reduction have gradually become an urgent problem to be solved. Lightweight polymer film materials are very effective in response to sound waves, and sound waves can easily cause vibration of the film, which can convert sound energy into vibration and film friction to achieve sound absorption. The application conditions of the film material are very harsh, that is, a support body is required to fix the film and the film needs to be tensioned. The film is very thin and easy to damage. The idea of this research is to transform the film into a bubble structure and use a large number of film bubbles to form a cavity structure material. As a unit of the sound absorption structure, bubbles can avoid damage to the film. In this paper, commercial polyvinyl chloride film bubble materials are used to prepare two kinds of film multicavity structure materials, and the sound absorption performance of this film multicavity structure material is studied. The research results show that this film multicavity structure material has very excellent broadband sound absorption performance, which changes the narrow band sound absorption properties of the usual film single cavity. The average sound absorption coefficient can reach 0.84 in frequency range from 500 Hz to 6400 Hz. This structural material has a single peak sound absorption curve at the middle and low frequency bands, which is the characteristic of resonance sound absorption. And at the middle and high frequency bands, it exhibits the characteristics of broadband sound absorption. The film multicavity structure material has both cavity sound absorption and broadband sound absorption characteristics.